Nutritive value of shrimp waste-meal and fly larva-meal (maggot-meal) in growing albino rats - ODUGUWA, O O; FANIMO, A O; ONIFADE, A A; ARIJE, A (The Indian Journal of Animal Sciences, 2013)
Growing albino rats of the Winster strain were used to determine the nutritive value of shrimp waste-meal(SWM) and maggot-meal (MM). Rats (24) were allocated to 4 equal groups of 6 rats each and fed ad lib. 4 different experimental diets. The first was the protein-free basal diet. The other 3 diets contained whole hen's egg (reference), shrimp waste-meal or maggot-meal as the only protein sources respectively. They supplied 100g/kg protein in the diets. Experiment lasted 21 days. Performance of rats on the MM protein was significantly higher than those fed SWM protein. There were no significant differences (P>0.05) in the relative weightsof lungs, kidneys, spleen and caecum. Rats on SWM, however, had lowest (P